Modelling spatio-temporal starch degradation patterns in apples during fruit growth - Scheerlinck, N; Escudero, C; Baker, R; Maini, P (2007)
This group, which is concerned with the applications of mathematics to agricultural science, was formed in 1970 and has since met at approximately yearly intervals in London for one-day meetings. The thirty-ninth meeting of the group, chaired by Professor N. Crout of the University of Nottingham, was held in the Kohn Centre at the Royal Society, 6 Carlton House Terrace, London on Friday, 30 March 2007 when the following papers were read.